Taxonomic revision of the Afrotropical species of the tribe Eudorylini (Diptera, Pipunculidae) - Földvári, Mihály (Zootaxa, 2013)
This paper revises the Afrotropical species of the tribe Eudorylini. The four genera (Claraeola, Clistoabdominalis, Dasydorylas, Eudorylas) present in the Afrotropical Region comprise 77 species (4, 4, 8 and 61 species respectively), 15 of them are new to science: Clistoabdominalis namibiensis, Dasydorylas bodocsi, D. okongoensis, Eudorylas angolae, E. barracloughi, E. brandbergensis, E. femoralis, E. gabela, E. hirsutus, E. lobus, E. pectinatus, E. pilulus, E. protumidus, E. rooibergensis and E. skorpionensis. Six new species name combinations are published: Claraeola hadrosoma, Clistoabdominalis crassus, Dasydorylas africanus, D. evanidus, D. minymerus and D. turneri. Type material for all available species was studied and species are (re)described in detail. Drawings of male and female terminalia are presented and an identification key to the males (only males were available in the majority of the species) is provided as well as individual species diagnoses for an easier species recognition. Eight new synonymies are proposed: Dorilas (Eudorylas) dorsalis and Dorilas (Eudorylas) apiculatus toDasydorylas evanidus, Pipunculus (Eudorylas) fractus to Eudorylas amitinus, Dorilas (Eudorylas) pusillus to Eudorylas diversus, Dorilas (Eudorylas) modicus to Eudorylas encerus, Dorilas (Eudorylas) megacanthus to Eudorylas garambensis and Dorilas (Eudorylas) quadratus and Pipunculus (Eudorylas) eremnoptera to Pipunculus mutillatus. A discussion on earlier methodology of species description within this group, in particular that of D. E. Hardy’s works, is given.